Legal and Constitutional Analysis of Federal Court Decision No. 230/Federal/2022: Regarding Marriage to Second Wife in the Province of Kurdistan - Baram, Sadi Hassan (As-Siyasi: Journal of Constitutional Law, 2024)
The Federal Court of Iraq issued Decision No. 230/Federal/2022, declaring the unconstitutionality of Article 12 of Law No. 15 of 2008, which grants the first wife the right to request a divorce if the husband marries a second wife. This article, enacted in the Kurdistan Region, was deemed to violate Islamic law and Article 2(a) of the 2005 Iraqi Constitution, which prohibits laws conflicting with the principles of Islam. The decision left behind a heated debate in the courts of the region between working with the article that the court cancelled or adhering to the court’s decision as the competent authority to interpret legal texts and resolve controversial issues. This study aims to examine the legal basis supporting the Federal Court’s decision with legal articles in force in the current Iraqi Personal Status Law, highlight the conflicts in the Kurdistan Region’s legal amendments, and address the decision’s strengths and shortcomings. Utilizing an analytical method, the study reviews and interprets relevant legal texts within the context of Iraqi Personal Status Law. the court, regardless of its supervisory authority, in addition to the justifications mentioned for the cancellation of Article 18 in the Kurdistan Region, is not infallible from shortcomings and observations; because it opposed in its decision what some sects have gone to, and deprived the wife of the right to demand separation under the pretext of violating the texts of the constitution and Islamic law. The study proved that the condition is not contrary to Islamic law as decided by the court; because it is a subject of disagreement among scholars, and it is also not considered contrary to the constants of Islamic rulings as stated in the decision of the Federal Court, because there is no jurisprudential consensus on such constants.